Vegetative provision of central hemodynamics and physical performance of middle distance sportswomen-runners - E. L. Mikhalyuk; S. N. Malahova; M. V. Didenko (Zaporozhye State Medical University, 2014)
Aims. To determine the autonomic provision of the central hemodynamics and physical performance in middle distance sportswomen-runners. Methods and results. A comprehensive survey of 34 sportswomen-sprinters, qualifications from II-III level to the IMS, was carried out. For the analysis of vegetative cardiovascular regulation mathematical methods of HRV were used. In middle distance sportswomen-runners with qualifications of MS-IMS parasympathetic link of autonomic nervous system, hypokinetic types of circulation, large quantities of physical performance and index of functional state prevail compared with sportswomen-runners with qualifications of CMS, I-st, II-nd and III-rd level. Conclusion. Correlation analysis showed a significant interconnection, indicating that the optimal vegetative providing of training process of middle distance runners is accompanied by hypokinetic TC and high digits of PWC170/kg and IFS.